How to Communicated in Generation Z Nurses - Saenung, Sureepeorn; Oumtanee, Areewan (Journal of The Royal Thai Army Nurses, 2020)
The objective of this qualitative research was to describe lived experiences of managing Generation Z nurses in nursing team of head nurses in an university hospital. The informants were head nurses who experienced managing Generation Z nurses in nursing team more than 3 years and Generation Z nurses have worked in their unit at least 3 people. Collecting data by indepth interview in purposive samplings 12 head nurses at an autonomous university hospital. Analyzing data by van Manen’s analysis (1990). The results of this research can describe how to communicated in Generation Z nurses in nursing team 5 points as follow : 1) Various channels to access communication 2) Tell topics clearly and no complexity 3) Easy to access all the time 4) Set priority communicated topics 5) Warn when use unappropriate social online technology.